Diagnostic Challenges of Primary Thyroid Lymphoma: A Case Report - Murdia; Hendra Zufry (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Primary Thyroid Lymphoma (PTL) requires a pathology confirmatory test to conclude the definitive diagnosis. Concerns arise when insufficient pathology specimen collection results in nonspecific pathological conclusion, in spite of the fact that the patient's clinical and radiological presentation strongly suggests a diagnosis of PTL. Patient with complaint of a painless lump in the neck that has been progressively getting bigger since a month ago. He also reported shortness of breath, intermittent fever, decreased appetite, weight loss of 5 kilograms, and general weakness. Physical examination showed a single and immobile palpated mass measuring ± 10x10x10 centimeters in the neck with hard consistency. Imaging concluded that the patient had a suspected malignant tumor with bilateral lymphadenopathy and cervical thoracic spondyloarthritis. Rapidly growing neck mass leads to heterogeneous diagnosis. Primary Thyroid Lymphoma (PTL) is suggested prominently in progressive thyroid mass expansion. The presented case was a male patient with clinical presentation showing a rapidly growing neck mass with an airway compression. While working on confirmatory testing of pathology examination (to define the type and immunohistochemistry characteristic of the tumor), the patient was treated adequately with supportive treatments. Supportive treatments for suspected PTL patients are important in securing airway patency, adequate fluid and nutritional intake, and prevent aspiration while working on confirmatory test. Diagnostic challenges of PTL not only limited to insufficient sample collection leading to unspecified pathologic results. Repetitive testing may result in delayed treatment and increase risk of complications.